A novel sports ball aerodynamics analysis tool: soccer ball design - Carré, M. J.; Barber, S. (Sports Technology, 2010)
A novel soccer ball design tool involving the optimisation of the aerodynamics is developed in this paper. The design tool allows the flight of different balls with various input conditions to be compared and the behaviour of new ball designs to be assessed. The tool was developed by combining CFD results with information from wind tunnel tests, trajectory testing, and player testing. Subsequently, the results (force coefficient data) were entered into a trajectory simulation programme. Various soccer ball designs were assessed using the design tool, and several conclusions drawn regarding aerodynamic optimisation. Two kick types are studied in this paper: curling, high-spinning kicks that are typically used for free-kicks, corners and long passes, and erratic, high-velocity, low-spinning kicks that are typically used for free-kicks, and shots on goal. The key physical phenomena relevant to both kick types were identified, and related to real game situations. Curling kicks were found to experience more swerve as the number of panels on the ball is increased. Low-spin, high-velocity kicks experience erratic side and lift forces that vary depending upon the surface geometry and the ball's orientation relative to the flight direction. The results were ultimately used to discuss the optimum design criteria for each type of kick, and two possible ball designs are suggested.